Short‐Term Cardiovascular Sequelae Following In‐Office Posterior Nasal Nerve Cryoablation - Jackson King; Lane D. Squires; Daniel Cates; Machelle Wilson; E. B. Strong; Toby Steele (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objective Evaluate the post‐procedural cardiovascular effects of posterior nasal nerve (PNN) cryoablation in comparison to inferior turbinate reduction (ITR). Methods Patients over 18 years of age who underwent in‐office PNN cryoablation or ITR via submucosal resection via radiofrequency ablation between 2019 and 2022 were enrolled. Cardiovascular parameters including systolic blood pressure (SBP), heart rate (HR), in addition to visual analog pain scale (VAS), were collected at baseline and perioperatively. Maximum changes and time to return to baseline were recorded. Results A total of 25 patients were enrolled in the study (16 PNN, 9 ITR). The median maximum change in SBP in the PNN and ITR groups was significant at 36.5 mmHg (IQR 22,50) and 11 mmHg (IQR 0,17) respectively (p = 0.007). The median time to return to baseline for SBP was significantly greater at 57.5 min (IQR 30,75) in the PNN group compared to 8.5 (IQR 0,34) in the ITR group (p = 0.026). The median duration of time post procedure to the maximal SBP recording for the PNN group was 32.5 min in comparison to 5 min in the ITR group (p = 0.083). No differences in HR were noted (p = 0.293). Conclusion PNN cryoablation is associated with greater and prolonged effects on SBP in comparison to ITR when using a similar in‐office anesthesia protocol. Surgeons offering this procedure should be aware of these effects when counseling patients and developing a protocol for post‐procedure monitoring. Level of Evidence 2